Expression patterns of cell adhesion molecules in bovine preimplantation embryos cultured in vitro - Sathanawongs,A. (Chulalongkorn University, 2015)
This study aimed to investigate gene expression patterns throughout preimplantation embryos and their comparative expression in morphological quality blastocysts using real-time RT-PCR. Bovine oocytes underwent maturation process, fertilized and were cultured in vitro. Degree of fragmentation and differentiation were the criteria to categorize day-7 blastocysts as of good and poor quality. All of the embryos from each developmental stage were used to quantify transcript abundance. It was found that E-cadherin was highly expressed in immature and mature oocytes, then it decreased at 2- to 16-cell stages, and later increased in morula and blastocyst stages. The ß-catenin transcript was highly abundant up to the 4-cell stage and further down regulated in the later stages. However, the transcript abundance of desmocollin 2 (DSC2) was high only at morula and blastocyst stages. The relative abundance of E-cadherin, ß-catenin and DSC2 mRNA in good quality blastocysts were statistically significantly higher than in poor quality blastocysts. Moreover, only the protein expression levels of E-cadherin and ß-catenin were significantly higher in good than in poor blastocysts. In conclusion, E-cadherin and ß-catenin are highly expressed in good quality bovine blastocysts. Therefore, they can be used as biomarker for blastocyst quality.